Perancangan Recruitment Management System Berbasis Web Menggunakan Metode Scrum (Studi Kasus: Pt Teknologi Informatika Solusindo) - Saputra, Suryana; Anwar, Chairul; Suryana (PT Jurnal Cendekia Indonesia, 2026)
PT Teknologi Informatika Solusindo still faces challenges in its recruitment management process, relying on methods such as face-to-face psychological tests (offline) and manual CV screening. This results in inefficiencies in managing applicant data and a time-consuming selection process. This study aims to develop a web-based recruitment management system that enhances the efficiency and effectiveness of the selection process, including CV screening and online psychological tests, enabling candidates to take the tests anytime and anywhere. The research method used includes interviews, literature study, questionnaires, and documentation. The system is developed using the Scrum methodology, which consists of several phases: Product Backlog, Sprint Planning, Sprint (Development), Sprint Review, and Sprint Retrospective. The outcome of this research is the Recruitment Management System (RMS) application, which accelerates decision-making in candidate acceptance and simplifies applicant data management. Recommendations include adding data analysis and automatic reporting features, providing training for the recruitment team, and conducting regular evaluations to ensure the system remains relevant and effective.